Catalytic Decomposition Of Methanol In Air Over Different Combinations Of Bimetallic Exchanged H-BEA Zeolites With Cobalt Chromium And Copper. - Bakar, M Zailani Abu; Bhatia, Subhash (Institut Piawaian dan Penyelidikan Perindustrian Malaysia, 2002)
The catalytic decomposition of methanol (MeOH) over single and different bimetallic exchange combinations or cobalt (Co), chromium (Cr) and copper (Cu) and zeolite Beta (H-BEA) was studied using a fixed-bed catalytic reactor in the temperature range 100"C-500.C, at MeOH feed concentration of 11,500 ppmv and gas hourly space velocity (GHSV)of 26,500 hour'1.